Current methods for the analysis of genetic case-control data: a review - Thomas, Duncan (Henry Stewart Talks, 2004)
Genotype vs. haplotype penetrance models, Likelihoods and fitting methods for case-control data, Bayesian smoothing and clustering models, Coalescent methods, Haplotype sharing methods, Haplotype blocks, htSNPs and the HapMap project
Archived at 2021/02/25